Solubility Prediction of Paracetamol in Water-Glycerol Mixtures at 25 and 30 ?C using the Jouyban-Acree Model - JOUYBAN, ABOLGHASEM; A.A. FAKHREE, MOHAMMAD; MIRZAEI, SHAHLA; GHAFOURIAN, TARAVAT; SOLTANPOUR, SHAHLA; NOKHODCHI, ALI (Asian Journal of Chemistry, 2010)
The solubility of paracetamol in water-glycerol mixtures at 25 and 30 ºC was determined using flask shake method. The generated data extended the solubility database for further computational investigations and was also used to assess the prediction capability of a trained version of the Jouyban-Acree model for solubility prediction in water-glycerol mixtures at various temperatures. The accuracy of the predicted solubilities was evaluated by the mean percentage deviation between the predicted and experimental solubilities. The overall mean percentage deviation of the Jouyban-Acree model for the back-calculated solubility data from the literature was 37.9 ± 21.9 %. The corresponding value for the predicted solubilities of paracetamol in binary mixtures using experimental values of paracetamol solubilities in water and glycerol was 15.6 ± 11.1 %.